2012
DOI: 10.1159/000334576
|View full text |Cite
|
Sign up to set email alerts
|

Uveal Melanoma: The Inflammatory Microenvironment

Abstract: Uveal melanoma is a highly malignant intraocular tumor with quite homogeneous tumor tissue and a diffuse leukocytic infiltration. In contrast with many other malignancies, the presence of infiltrating macrophages and T cells is associated with a poor prognosis rather than a good one. The clear link between inflammation and cancer in this malignancy provides a paradigm for macrophage plasticity and function. Macrophages in uveal melanoma have an M2-like phenotype and are associated with the loss of one specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 97 publications
5
59
0
3
Order By: Relevance
“…Tregs may, thus, not be the main suppressor cells at the tumor site, whereas other suppressive cells may hamper antitumor immunity locally in our model. In line with such an assumption, we have recently shown that type 2 macrophages infiltrate massively the most aggressive metastases (21), which is consistent with observations in human melanoma biopsies (26)(27)(28). In contrast, the proportion of Tregs among CD4 + T cells was increased in the spleen and TdLNs of MT/ret mice without vitiligo, in agreement with the accumulation of Tregs observed in TdLNs few days after tumor cell implantation in several transplanted tumor models (7).…”
Section: Discussionsupporting
confidence: 90%
“…Tregs may, thus, not be the main suppressor cells at the tumor site, whereas other suppressive cells may hamper antitumor immunity locally in our model. In line with such an assumption, we have recently shown that type 2 macrophages infiltrate massively the most aggressive metastases (21), which is consistent with observations in human melanoma biopsies (26)(27)(28). In contrast, the proportion of Tregs among CD4 + T cells was increased in the spleen and TdLNs of MT/ret mice without vitiligo, in agreement with the accumulation of Tregs observed in TdLNs few days after tumor cell implantation in several transplanted tumor models (7).…”
Section: Discussionsupporting
confidence: 90%
“…Aberrations were observed in all chromosomes, with chromosomes 1, 3,6,8,13,15,16, and Y being altered in at least 15% of the tumors. Aberrations were more common and more complex in previously irradiated tumors (significant for chromosomes 5 [P ¼ 0.004] and 13 [P ¼ 0.04]).…”
Section: Methodsmentioning
confidence: 98%
“…Tumourpromoting inflammation Lymphocytes Macrophages Dendritic cells Varying densities of tumour infiltrating lymphocytes and macrophages; both associated with worse prognoses [54][55][56][57][58][59] In the following paragraphs, the major molecular pathway defects and the most common chromosomal alterations in UM development will be summarised.…”
Section: Enabling Characteristics 1 Genome Instability and Mutationmentioning
confidence: 99%